Protection Relevance of the Execution of Separatic Creditors Based on Pancasila Justice - Gregorius Yoga Panji Asmara (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
The execution of the execution by separatist creditors without going through court adjudication as stipulated in Article 55 and Article 56 of Act No. 37 Of 2004 is contrary to Pancasila justice. The method used is the normative juridical method. Based on the data obtained, it can be seen that the implementation of bankruptcy executions as regulated in Article 55 and Article 56 of Act No. 37 of 2004 prioritizes the interests of separatist creditors, this is further complicated by the existence of a legal culture that shows that bankruptcy executions are guaranteed with mortgage without having to go through anmaning in court, the meaning of the debtor's insolvency should be a trial in court or through anmaning regarding the debtor's ability to pay off his debt, not solely based on the analysis and views of the separatist creditors. This is clearly implicitly based on Article 28D of the 1945 Constitution of the Republic of Indonesia and automatically contradicts the value of Pancasila social justice.